THE SUPERNATURAL ELEMENTS REFLECTED IN WASHINGTON IRVING’S TALES OF A TRAVELER - Edi Ardian (UIN Alauddin Makassar, 2016)
AbstractWashington Irving describes the Supernaturalism in Tales of a Traveler. He is one of the earliest American writer of Imaginative literature in the age of Romanticism and it happened of France Revolution that fulfilled by the enthusiasm and liberty. This research is going to find some words to indicate the supernatural element in romantic era. Based on the previous explanation, the writer formulates the problems as follow: 1) Why Washington Irving as the Romantic writer does write the supernatural elements in his essays and 2) What are the words to indicate of supernatural elements in his essays. The analysis finds out that the supernatural gothic and symbol that he described in Tales of a Traveler is one of satire or criticize of the condition in his era, that happened French revolution and there are many conflict in Europe that make people want move to the new place. Therefore, we can call by the transition era. The mysticism is one of characteristic of the romantic era, so the mysticism close meaning with the supernatural that the extra of natural. Irving made satire as criticize of the condition that filled any conflict in Europe after French revolution to make people individualistic.AbstrakThe Supernatural Elements Reflected in Washington Irving’s Tales of A Traveler. Washington Irving menggambarkan hal-hal yang berhubungan dengan dunia supernatural di dalam karyanya yang berjudul Tales of Traveler. Dia termasuk penulis pertama Amerika yang sastranya imaginatif pada Era Romantis yang terjadi pada saat revolusi Ferancis yang ditandai dengan anthusiasme dan kebebasan. Berdasarkan penjelasan ini maka dapat dirumuskan dua pertanyaan yaitu: 1) mengapa Irving di dalam karyanya pada era romantis ini menulis tentang supernatural pada karyanya 2) Apa saja perkataan Irving yang menunjukan hal-hal supernatural dalam karyanya. Maka analisis ini menemukan bahwa supernatural gothic dan symbol yang tergambar didalam Tale of Traveler adalah salah satu sindiran atau keritikan terhadap kondisi yang terjadi pada era revolusi Perancis. Terjadi banyak konflik di Eropa yang membuat orang ingin pindah tempat yang baru. Oleh karena itu disebut dengan era transisi. Karya yang berbau mistik merupakan salah satu karakteristik pada era romantis ini, mistik dekat maknanya dengan supernatural yang berhubungan dengan di luar hal alami. Irving menyindir dan mengkritik terhadap konflik yang terjadi di Eropa pasca revolusi perancis yang membuat orang lebih individualistik.